Experience Of Baha Attract System In Malaysia - Salahuddin, Nor Azirah; Goh Bee See; Abdullah,Asma. (EBSCOhost, 2024)
Introduction: Bone conduction implants have been used internationally for decades. It is accepted as the mainstay treatment for conductive and mixed hearing loss for rehabilitation. It is commonly indicated for canal atresia, chronic ear infection as well as single-sided deafness. The mechanism of bone anchored hearing aid is by a process called direct bone conduction. The Baha Attract system is a transcutaneous bone conduction implant which uses magnet retention to connect the sound processor with the osseointegrated implant. Objective: We would like to evaluate the outcome of the system which involved nine patients particularly in terms of surgery, complication and clinical performance. Design: Case series. Case presentation: This is a retrospective review of medical files from year 2014-2016 for patients using Baha Attract system in Otorhinolaryngology clinic, UKMMC. A total of 9 patients were identified. The main indication in our series is microtia with canal atresia /stenosis which accounts for about 67% (n = 6) and 33% (n = 3) were implanted due to single sided deafness (SSD). The mean preoperative unaided air conduction threshold (0.5 kHz, 1 kHz, 2 kHz frequencies mean) was 81 dB (range 47-120). The average postoperative BAHA-aided sound field hearing threshold was 27.6 (range 12-45) dB. The overall mean functional gain was 53.1 dB (range 20-108). Discussion: Baha Attract system has the advantages in terms of aesthetic and hygienic concern. It was designed with a single- point transmission for better and efficient sound transmission by focusing the vibration in a single point. This design is preferred compared to multiple screws as the vibration energy will spread over several contact points resulting in lower transmission efficiency. The Baha Attract operation is a minor procedure and safe to be performed with minimal post-operative complications. From audiological perspective, majority of current studies showed good clinical performance with the Baha Attract system. Conclusion: Baha Attract system is a new innovation that has proven to be an effective hearing device. The surgery is safe in adult as well as paediatric patients with minimal minor complications that can be treated conservatively. The overall mean functional gain was 53.1 dB.